HUBUNGAN MOTIVASI DENGAN PERILAKU KESIAPAN KEHAMILAN PADA IBU PRIMIGRAVIDA DI DESA RAJEG KABUPATEN TANGERANG BANTEN - Indah Nurmala Sari; Nuryani; Lastri Mei Winarni (Nusantara Hasana Journal, 2022)
Every woman who has healthy reproductive organs, who has experienced menstruation, and has sexual intercourse with a healthy man is likely to experience pregnancy. In order for the process of pregnancy and childbirth to run smoothly, it is necessary to prepare and care for pregnant women, with the hope that it will form and increase the independence of the mother in caring for and maintaining her health. This type of research is quantitative research. The research design used a descriptive correlation type, with a cross-sectional approach. The population in this study were pregnant women with their first child in the district of Rajeg, Tangerang Regency as many as 50 people in the village of Rajeg. The sampling technique used is total sampling. The results of bivariate analysis using Chi-square obtained p-value <0.05, namely 0.003 which means that the HO hypothesis is rejected that there is a significant relationship between motivation and pregnancy readiness behavior in Primigravida mothers in Rajeg Village, Tangerang Regency, Banten. There is a significant relationship between motivation and pregnancy readiness behavior in Primigravida mothers in Rajeg Village, Tangerang Regency, Banten.